(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2009)
Key words: diagonal artery; age-at-death of subject; atherosclerosis doi: 10.3329/jcmcta.v19i1.3847 Journal of Chittagong Medical College Teachers’ Association 2008: 19(1):20-22